STRATEGI KOMUNIKASI DAKWAH BERBASIS KEARIFAN LOKAL UNTUK MEMINIMALISIR KONFLIK SOSIAL DALAM KOMUNITAS MUSLIM ACEH - Zulfikar, Zulfikar Arahman (AT-TAWASUL, 2023)
This study aims to develop a local wisdom-based da’wah communication strategy to minimize social conflicts in the Muslim community of Aceh. The background of this research stems from the importance of da’wah communication in solving social issues, particularly in communities with strong local wisdom, such as Aceh. The methodology used in this study is library research, collecting and analyzing relevant literature on da’wah communication, local wisdom, and social dynamics in Aceh. The research results show that the integration of Islamic values with local traditions, such as deliberation and the Mukim Customary Law, can enhance the effectiveness of da’wah in creating social harmony. The active role of local leaders, both religious and customary figures, is a determining factor for the success of this strategy. This research contributes significantly to developing contextual and sustainable da’wah approaches, offering a model that can be applied in other regions facing similar social challenges.